Aldehyde-induced DNA and protein adducts as biomarker tools for alcohol use disorder - Heymann, Helen M. (Trends Mol Med, 2018)
Alcohol use disorder (AUD) screening frequently involves questionnaires complemented by laboratory work to monitor alcohol use and/or evaluate AUD-associated complications. Here, we suggest that measuring aldehyde-induced DNA and protein adducts produced during alcohol metabolism may allow an earlier detection of AUD and AUD-associated complications compared with existing biomarkers. Using aldehyde-induced adducts to monitor AUD may also be important when considering that approximately 540 million people bear a genetic variant of aldehyde dehydrogenase 2 (ALDH2), predisposing this population to aldehyde-induced toxicity with alcohol use. We posit that measuring aldehyde-induced adducts may provide a means to improve precision medicine approaches, taking into account lifestyle choices and genetics to evaluate AUD and AUD-associated complications.